Environmental predictors to falls in the elderly: an integrative review (Research, Society and Development, 2021)
Objective: To identify in the literature the environmental predictors of falls in the elderly. Method: an integrative literature review included investigations developed that addressed falls in the environment of the elderly without a time frame. Revisions, studies without specific analyzes for falls in the environment, and studies with the elderly population in special situations were excluded. The Lilacs, Scopus, CINAHL, Web of Science and PubMed databases were consulted, using the descriptor accidents by falls, their correspondents in Portuguese and the Boolean operator AND. To assess the quality of the studies, the Newcastle-Ottawa scale was used. After applying the inclusion and exclusion criteria, 12 articles were selected. Results: Seven studies were found: three cross-sectional studies and four cohorts. The sample sizes ranged from 18 to 1,243 elderly people and year of publication from 1998 to 2017, the most recent of which were 2013, 2015 and 2017. The studies addressed balance and gait, self-reported falls and the prevalence of environmental risks in their majority. Conclusion: It was evidenced that the individual and environmental multifactors predispose elderly to falls.